A rare type 1 hypersensitivity to latex in dental treatment setting and management - Bugude, Shiva Shankar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Latex gloves are considered to be the most effective barrier to blood-borne pathogens. Latex allergies in health professionals and patients are not quite uncommon. Reactions to latex gloves can vary from minor irritation to allergic reactions. In finished latex products, protein allergens account for up to 2 percent by weight [1]. Latex allergies clinically can manifest as contact dermatitis or immediate type I hypersensitivity or delayed type IV hypersensitivity. This scientific article presents two cases of latex allergy type I hypersensitivity and uneventful management.